2001
DOI: 10.1038/sj.ejcn.1601268
|View full text |Cite
|
Sign up to set email alerts
|

The energy expenditure of postmenopausal women classified as restrained or unrestrained eaters

Abstract: Objective: Restrained eating is a common dietary practice among individuals who are attempting to prevent weight gain, but little is known about differences in energy physiology and regulation between restrained and unrestrained eaters. We investigated this issue in non-obese free-living postmenopausal women classified as longterm restrained (n ¼ 26) or unrestrained (n ¼ 34) eaters group matched for body mass index (BMI). Measurements: Measurements were made of total energy expenditure (TEE), resting energy ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 31 publications
1
4
1
Order By: Relevance
“…In identical twin pairs, a restrictive/overeating eating style predicted excess weight even when genetic background was controlled for [42]. Interestingly, restrained eaters are not consistently found to be in energy deficit [43], as documented by stable lifetime maximum weight in this study and resting energy expenditure in other studies [44][45][46]. However, alterations in hormones such as ghrelin suggest a biological impetus for weight gain despite energy balance -a loophole of sorts in the body weight regulatory system.…”
Section: Discussioncontrasting
confidence: 42%
“…In identical twin pairs, a restrictive/overeating eating style predicted excess weight even when genetic background was controlled for [42]. Interestingly, restrained eaters are not consistently found to be in energy deficit [43], as documented by stable lifetime maximum weight in this study and resting energy expenditure in other studies [44][45][46]. However, alterations in hormones such as ghrelin suggest a biological impetus for weight gain despite energy balance -a loophole of sorts in the body weight regulatory system.…”
Section: Discussioncontrasting
confidence: 42%
“…Platte et al (17) found that resting metabolic rate was reduced significantly in restrained eaters. It should be noted that, similar to our findings, other investigators have failed to find an effect of restrained eating behavior on resting metabolic rate (18, 19) or the thermic effect of food (17, 18).…”
Section: Discussionsupporting
confidence: 90%
“…Individual differences in spontaneous physical activity and NEAT have important implications for energy balance (89), but the mechanisms underlying spontaneous physical activity and NEAT are still unknown. A study of the response to overfeeding in self-reported restrained and unrestrained eaters indicates that restrained eaters have reduced NEAT, which may contribute to enhanced susceptibility to weight gain in restrained eaters (8). In mice, levels of spontaneous physical activity cluster within strain (22,146), and in humans, within families (22,155,163), suggesting that inherent differences may account for variance in NEAT.…”
Section: The Physiological Context Of Measurement Of Spontaneous Physmentioning
confidence: 99%